Peptide mediated formation of noble metal nanoparticles — controlling size and spatial arrangement. (October 2017) - Corra, Stefano; Shoshan, Michal S; Wennemers, Helma
Highlights: Peptides are attractive additives for the controlled formation of metal nanoparticles. Combinatorial methods are valuable for identifying peptides for NP formation. Understanding the interplay between the peptide and the nanoparticle is important. Self-assembling peptides can control the spatial arrangement of nanoparticles. Abstract : Over the past two decades, peptides have expanded the toolbox of additives for the preparation of noble metal nanoparticles. Their functional and structural modularity and accompanying molecular recognition and self-assembly properties offer unique opportunities for the controlled formation of NPs. Within this review, we highlight recent examples for the use of peptides to control a) the size and shape of NPs and b) the spatial arrangement of NPs. The article focuses on examples where the peptides are directly involved in the bottom-up synthesis of the noble metal NPs.